(untitled) (Global Journal of Science Frontier Research, 2023)
Globally the cost of hard tissue repair and regeneration is in the hundreds of billions of dollars every year and as the population ages this demand has grown significantly Structures made of calcium phosphate minerals such as bone and teeth are considered to be hard tissues Techniques for regenerative medicine and smart biomaterialbased tissue engineering have the exciting potential to fill this critical need By engineering the material s responsiveness to internal or external stimuli smart biomaterials and constructs can have instructive inductive triggering stimulating or stimulating effects on cells and tissues They can also have intelligently tailored properties and functions that can encourage tissue repair and regeneration Smart scaffolds and stem cell constructs for bone tissue engineering intelligent medication delivery systems to improve bone regeneration and intelligent dental resins